Educational Experience and Instructional Design Effectiveness Within the Community of Inquiry Framework - Wilson, Emerald C.; Berge, Zane L. (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2023)
Within its 20 years of development, the Community of Inquiry (CoI) framework has become the most widely used theoretical framework in e-learning. It is considered in much of the distance education literature to be a robust collaborative-constructivist process model that uses three essential elements to interpret educational experience: cognitive presence, teaching presence, and social presence. Widespread use of the CoI framework has resulted in several criticisms, such as having no guidelines for implementation, no incorporation of assessment and evaluation metrics, and no widespread consensus on the current model’s ability to represent all the contributing factors that promote a positive educational experience. However, there is an opportunity to overcome these shortcomings, some of which may exist, and to use the CoI’s extraordinary strength in creating a positive education experience, by adding instructional design effectiveness. The purpose of this combination of a literature review and opinion is to present the CoI framework and its major controversies to shine a light on its importance as one approach to designing critical parts of e-learning. Additionally, given the CoI’s purpose of creating a positive educational experience, this paper argues to make explicit to instructional designers and instructors the need to address using the CoI framework within an effective overall design.